Urban Continuity: the urban regeneration of Fordsburg through integrating the mall (the Oriental Plaza) and the grid (urban fabric) - Da Silva, Paulo (My University, 2020)
This research explores urban continuity in a part of Johannesburg. The objective is to broadly investigate the history of Fordsburg, its role as a mixed use precinct and to address the issues caused by 1970s imposed Modernism. Cities reveal the relationship between the individual and the greater whole. They bring people together for the mutual benefit and support of each other. This demonstrates the co-existence of different layers of history and embodies a level of continuity - this is the first reference to the title of this research. Continuity does not signify a linear one after the other system, but rather it is an interpretation of time and of physical space, in which the past continues to exist in the present. Michael Focault (1980), an historian and philosopher, states: “space is history.” We all have relationships with the city that rely on the physical formation of the city and its civic history to determine our identities. It is a complex process that is best understood through urban morphology. Oliveira et al (2015) states that there is more to urban morphology that also reveals the elements of a city. These elements form typologies which have genealogies (Dovey et al, 2016). Continuity also applies to the urban patterns produced in cities, which are revealed from examining the physical environment (Alexander et al, 1977). The physical environment, which is an element of urban morphology, focuses on the act of habitation and spatial principles (von Meiss, 2015). It is an appropriate subject because it forms the basis for urbanity and the background atmosphere for living in possible happiness and comfourt. The physical urban environment has codes and conventions that need to be learned, understood and challenged. Fordsburg, a metropolitan suburb in Johannesburg which embodies decades of history and functions within two extremes of Johannesburg’s physical environment: it possesses some of the best qualities of urbanity and also some of the poorest. The site of these urban extremes is the Oriental Plaza: which is a modernist suburban mall masquerading as an urban market. To the west of the mall exists a bastion of urbanity and to the east of the mall is an environment that has become desolate and lost. Auge (1995) and Trancik (1986) describe poor urban spaces as anti-space or lost space, that doesn’t not provide any real benefit for urban living. The challenge is therefore to understand how to connect the eastern and western urban fabric, regenerate the lost urban spaces and stitch urban typologies together meaningfully. The principles of urban continuity (Dewar et al, 1992) offer an appropriate design tool to promote positive change. The principles of urban continuity also offer to the opportunity to realize the mall as a permeable catalyst for Fordsburg’s connection to Johannesburg’s eastern fringe
Research report submitted in fulfillment of the requirements for the Masters of Urban Design, Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2020